Replacement of Missing Upper 2nd Premolar by Short Implant: A Case Report (BIRDEM Medical Journal, 2012)
Compared to previous generations when tooth loss was common, modern dentistry has made it possible for people to keep their teeth healthy and attractive for their entire lives. Today, dental implants can replace missing teeth. Although the concept of a tooth implant is not new, advances in technology have improved the treatment process and the longevity of implants. Dental implants can be used for single tooth replacements, support for a permanent bridge, or as attachments to anchor a full denture securely to the jaw. The clinical reality is that many potential implant patients have limited bone height. When placing longer implants, the maxillary sinus and inferior alveolar nerve often present risk. Although bone grafting sinus lifts procedures help alleviate this risk, patients may still avoid treatment because of the financial costs and time for grafting procedures. Additionally, bone grafting procedures have their own inherent risks and morbidities which patients often find unacceptable. While Short Implants afford simpler and consistently more predictable treatments, which can significantly increase a patients acceptance of implant treatment. With the use of Short Implants, patients with limited bone height can often avoid the inherent risks and costs associated with bone grafting procedures. Additionally, the extended healing time and cost of bone grafting procedures are eliminated. This article describes a simple approach for placement of short implant in maxillary premolar and its subsequent restoration.DOI: http://dx.doi.org/10.3329/birdem.v2i2.12327(Birdem Med J 2012; 2(2):116-120)